Traumatic Brain Injury and Psychopathic Features Among Juvenile Offenders: Does it Matter Which Traits? - Olson, Lindamarie (International journal of offender therapy and comparative criminology, 2023)
Psychopathic traits and a history of traumatic brain injury (TBI) are common among imprisoned individuals. Although previous research has examined correlates of TBI among juvenile offenders, little research has explored the relationship between psychopathic traits and TBI among this population. Study objectives included: (1) examine the association between the history of a TBI and psychopathic traits among juvenile offenders and (2) determine if the history of a TBI predicts the manifestation of different psychopathic factors among juvenile offenders. Cross-sectional data from the Multidimensional Youth Residential Inventory consisted of 226 juvenile offenders. Bivariate and multivariate analyses were conducted. Results of linear regression analyses showed that history of a TBI significantly predicted callous unemotional and impulsive irresponsible traits. Clinical implications suggest early intervention is needed to treat the potential long-term effects of TBIs and the development of psychopathic traits. Recommendations for further research are discussed.